Case Report: No Evidence of Intracranial Fluid Shifts in an Astronaut Following an Aborted Launch - McGregor, Heather R.; Hupfeld, Kathleen E.; Pasternak, Ofer; Wood, Scott J.; Mulavara, Ajitkumar P.; Bloomberg, Jacob J.; Hague, T. Nick; Seidler, Rachael D. (Frontiers in Neurology, 2021)
Spaceflight induces lasting enlargement of the brain’s ventricles as well as intracranial fluid shifts. These intracranial fluid shifts have been attributed to prolonged microgravity exposure, however, the potential effects of hypergravity exposure during launch and landing have yet to be elucidated. Here we describe a case report of a Crewmember who experienced an Aborted Launch (‘CAL’). CAL’s launch and landing experience was dissociated from prolonged microgravity exposure. Using MRI, we show that hypergravity exposure during the aborted launch did not induce lasting ventricular enlargement or intracranial fluid shifts resembling those previously reported with spaceflight. This case study therefore rules out hypergravity during launch and landing as a contributing factor to previously reported long-lasting intracranial fluid changes following spaceflight.